Kajian metode the empirical area reduction untuk prediksi distribusi endapan sediment pada beberapa waduk dengan karakteristik berbeda - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Reservoir sedimentation as well as its sediment distribution during its time of reservoir operation is very related to its useful lifetime of reservoir. Reservoir sedimentation is a complicated subject, and techniques proposed to calculate sediment distribution are many and varied, and mainly empirical. Among of the existing methods found in the literature is the one proposed by Borland and Miller (1958), which is known as the empirical area-reduction method. The method has to take into account of the reservoir classification as one of four standard types as being proposed by the method. Sediment distribution data obtained from different reservoirs with different characteristics, i.e., reservoir with small, medium, and large capacity, as well as reservoir with short and long time of operation, are used as a base of comparison to the distribution calculated by the empirical method. The data are obtained from Mrica, Sermo, Wonogiri, and Selorejo reservoirs. From the investigation done here, it can be concluded that the empirical method proposed by Borland and Miller (1958) can be used to estimate sediment distribution of different characteristics of reservoirs, either for small, medium, and large reservoirs capacity. A problem is identified only for a small reservoir with short time of operation (as shown from Serino reservoir data). However, when the time of reservoir operation increases, the method can be used to predict sediment distribution